Evaluation of Teacher Professional Development Program at Elementary School 34 South Pontianak - Sukmawati Sukmawati (JETL (Journal of Education, Teaching and Learning), 2022)
The purpose of conducting this research was to evaluate the implementation of the teacher professional development program at SDN 34 Pontianak Selatan. It hopes that this research will be helpful to provide input and suggestions for the professional development of teachers in general and in particular at SDN 34 Pontianak Selatan. This development can become a role model for schools in the vicinity. This research used a descriptive method. Descriptive is a problem-solving procedure that is investigated by describing the state of the object of the research at present as it is. Based on the opinion above, the researcher used a descriptive method by looking for data about the implementation of the Teacher Professional Development Program at SDN 34 Pontianak Selatan by using the Goal-Oriented Evaluation Model. The data obtained in this research is narrative sentences, documents, and images from observations. Data collection is carried out on an ongoing basis through interviews, observations, and document studies.